Approaches to Macrofinancial Surveillance in Article IV Reports. (Policy Papers; Policy Paper ;, 2017)
The Fund has made good progress over the past two years in integrating macrofinancial analysis into Article IV surveillance for a wide range of members. Building on past work to enhance financial sector analysis, Fund staff has sought to develop a consistent and forward-looking view on how the financial sector affects each member's economic outlook with the aim of strengthening staff's capacity to provide advice on macro-critical questions. The focus has been on developing a fuller understanding of macrofinancial linkages, and applying this analysis to inform policy advice. Staff has sought to articulate the role of the financial sector in the macroeconomic baseline, and to integrate the financial sector into the risk assessment, taking into account both the impact of macro shocks on the financial sector as well as the effect of financial shocks on macroeconomic stability. Strengthening the analytical foundations of this work has helped staff provide advice in all policy areas, including financial sector policies. Staff has tailored macrofinancial analysis to the circumstances of a diverse set of economies. Area departments have taken the lead in selecting 66 economies for enhanced macrofinancial coverage and in identifying topics, drawing on targeted support from functional departments. The choice of coverage has included legacies from the global financial crisis-such as deleveraging and stretched balance sheets in advanced economies and some emerging markets-and more recent challenges such as commodity price shocks, especially in low income countries, and the risks of housing booms. The financial sector's contribution to growth and inclusion has become an important question in countries across all income groups. Staff sees benefits in mainstreaming this approach across the membership, while continuing to address analytical gaps and adapting to new challenges. The work of the past two years has underscored the criticality of macrofinancial analysis for a diverse range of members, and laid the basis for progressively mainstreaming macrofinancial surveillance across the membership. Building on this progress, staff sees scope for the Fund to deepen its understanding of the macroeconomic effects of financial shocks, to better adapt microprudential and macroprudential policy advice with an assessment of macro-critical risks including systemic risk, and to deepen the analysis of outward spillovers. Staff will also need to continue to adapt the focus of analysis and tools, and seek relevant data, as economic challenges evolve.